Insights on acupuncture as a complementary method for therapeutic management of intervertebral disc diseases in dogs - Liliana Carpinisan; Gabriel Radbea; Domnica Bajinaru; Alina Ghise; Adrian C. Stancu; Petronela Mihaela Rosu; Denisa Sorescu (Medicamentul Veterinar, 2020)
Intervertebral disc disease (IVDD) is a broad term, involving the degeneration of intervertebral disc structures and subsequent herniation of disc material in the spinal canal, but also clinical neurological disease due to disc herniation. Spinal cord compression syndrome results in symptoms that can range from local hyperesthesia to rear limbs paralysis and / or genitourinary dysfunction. Depending on the clinical signs and the location of condition, the therapeutic approach varies from conservative to surgical. Classical medicine is often not enough to normalize the patient, which is why alternative methods are recommended, including acupuncture (AP). Following acupuncture in 6 dogs that underwent hemilaminectomy or laminectomy consecutive of thoracolumbar IVDD (Hansen I; Hansen II) the observed effects ranged from insignificant to motor recovery, depending on the degree of spinal cord damage and the involvement of the owners in the post-surgery recovery. The results were generally evident after a few acupuncture sessions and were influenced by the characteristics of each patient.